Pengaruh CEO Narcissism dan Audit Quality terhadap Green Accounting pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2024 - Ribka Angely Yaputri Goni; Richard Friendly Simbolon; Mila Susanti (Journal of Innovative and Creativity, 2025)
This study analyzes the influence of CEO narcissism and audit quality on green accounting in companies listed on the Indonesia Stock Exchange in 2024. The research method used is a quantitative approach with multiple linear regression analysis on 78 companies selected through purposive sampling. CEO narcissism is measured by the proportion of CEO photos displayed in annual reports, while audit quality is measured by the auditor's affiliation with a Big Four accounting firm. Regression tests found that CEO narcissism and audit quality have a negative and significant effect on green accounting, both partially and simultaneously. This indicates that the higher the CEO's narcissism and the stricter the audit quality, the lower the level of disclosure of green accounting practices. Overall, the combination of the two plays a significant role in determining the level of transparency and accountability in a company's sustainability reporting.